2017
DOI: 10.1086/692667
|View full text |Cite
|
Sign up to set email alerts
|

Quality-Based Explanations of Incumbency Effects

Abstract: Empirical studies of incumbency effects continue to accumulate, but progress in explaining these findings is modest. I introduce a simple framework that clarifies how differences in candidate characteristics (i.e. quality) could account for empirical findings of incumbency effects based on regression discontinuity designs (RDD). The key observation is that although RDD ensures that marginal winners and losers of close elections are comparable, the candidates who compete in the next election may differ for many… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 41 publications
2
13
0
Order By: Relevance
“…See, for example, Almendares and Le Bihan (), Ashworth (, ), Ashworth and Bueno de Mesquita (, ), Banks and Sundaram (), Besley (), Besley and Burgess (), Besley and Prat (), Canes‐Wrone, Herron, and Shotts (), Coate (), Daley and Snowberg (), Eggers (), Fox and Jordan (), Fox and Stephenson (, ), Fox and Van Weelden (, ), Gehlbach (), Gordon, Huber, and Landa (), Lohmann (), Maskin and Tirole (), Myerson (), and Persson and Tabellini ().…”
mentioning
confidence: 99%
“…See, for example, Almendares and Le Bihan (), Ashworth (, ), Ashworth and Bueno de Mesquita (, ), Banks and Sundaram (), Besley (), Besley and Burgess (), Besley and Prat (), Canes‐Wrone, Herron, and Shotts (), Coate (), Daley and Snowberg (), Eggers (), Fox and Jordan (), Fox and Stephenson (, ), Fox and Van Weelden (, ), Gehlbach (), Gordon, Huber, and Landa (), Lohmann (), Maskin and Tirole (), Myerson (), and Persson and Tabellini ().…”
mentioning
confidence: 99%
“…This issue worsens whenever the empirical strategy does not properly parse out quality differences (i.e., φ > 0) either because researchers do not properly approximate the 50 − 50 threshold (seeHyytinen et al, 2017 for empirical evidence) or the electorate holds systematically different opinions of incumbents and challengers at the threshold(Eggers, 2017;Fowler, 2017).21 When candidates can campaign on common good or divisive issues, others have shown that higher degree of electoral competition can harm the electorate (e.g.,Lizzeri and Persico, 2005).…”
mentioning
confidence: 99%
“…At a deeper level, the present work joins a few papers proposing a new link between theory and empirics. Rather than focusing on comparative statics (Ashworth and Bueno de Mesquita ), these studies (re)assess in various contexts what empirical estimates actually measure (e.g., Eggers for the incumbency effect; Wolton for special interest group influence). This approach, broadly defined, uses formal reasoning to rethink empirical counterfactuals .…”
Section: Resultsmentioning
confidence: 99%